Method for improving electrolyte infiltration efficiency of large-size power battery

By performing surface micro-oxidation treatment on conductive carbon and using step-by-step liquid injection method, the problem of difficult infiltration of electrolytes in large-size power batteries is solved, and the electrolyte is rapidly infiltrated and efficient diffusion at the electrode interface is achieved. It is suitable for a variety of battery types and reduces production costs.

CN119542528APending Publication Date: 2025-02-28DONGFENG MOTOR GRP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411392054.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Large-size power batteries have difficulties in the electrolyte infiltrating process, resulting in limited battery performance performance, and the existing technology methods are poor in universality, complex processes, and long time, which increases production costs.

Method used

By performing surface micro-oxidation treatment on the conductive carbon, the surface energy of the interface between the electrolyte and the electrode is reduced, and two electrolytes with large concentration differences are used for step-by-step injection, forming a diffusion gradient to accelerate the diffusion of the electrolyte inside the electrode.

Benefits of technology

It realizes rapid and efficient soaking of large-size power battery electrolyte, shortens production time, reduces production costs, and is suitable for different types of battery shells, such as cylindrical, soft-pack and square-shell batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542528A_ABST
    Figure CN119542528A_ABST
Patent Text Reader

Abstract

The invention discloses a method for improving the electrolyte infiltration efficiency of a large-size power battery, and belongs to the technical field of power batteries, and the method comprises the following steps: carrying out surface micro-oxidation treatment on conductive carbon, so that the contact angle between the conductive carbon and an electrolyte used by a selected battery model is reduced to meet a preset requirement, and obtaining surface micro-oxidation conductive carbon; the surface micro-oxidation conductive carbon is assembled into a large-size power battery according to a selected battery model; liquid injection is performed twice in batches, a pure solvent is injected for the first time, and a high-concentration electrolyte is injected for the second time; and after packaging, standing at 45 DEG C to finish the infiltration process. Only a small amount of conductive carbon on the electrode plate is optimized, then electrolyte with different concentrations is used for step-by-step liquid injection, and surface micro-oxidation can be completed only in 5-30 min. The existing battery production process does not need to be greatly changed, and the input cost is relatively low. More efficient electrolyte infiltration is realized, the production time is shortened, and the production cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of power battery technology, specifically to a method for improving the electrolyte wetting efficiency of large-size power batteries. Background Technology

[0002] Improving battery energy density is a key strategy for alleviating range anxiety in electric vehicles. Currently, the performance of ternary cathodes and lithium iron phosphate batteries is approaching theoretical values, making it difficult to further increase energy density at the material level. In recent years, battery manufacturers have continuously optimized battery structures to improve space utilization and increase cell size; at the electrode level, they have reduced the mass proportion of inactive components and increased electrode compaction and areal density. However, as battery size increases, the increase in compaction and areal density leads to difficulties in electrolyte wetting and longer wetting paths. Furthermore, high-compacted electrodes result in lower electrolyte retention, limiting battery performance and even affecting safety and cycle life. While increasing wetting time can improve wetting, it also increases manufacturing time and production costs.

[0003] In the early stages of development, battery R&D engineers primarily optimized electrode wetting by improving injection methods, refining winding processes, adding electrolyte additives (surfactants), and modifying separators, achieving significant improvements. Currently, strategies for improving electrolyte wetting in large-size batteries (generally referring to cells with a height greater than 200mm) fall into two main categories: physical methods and electrochemical methods. Physical methods mainly accelerate electrolyte diffusion within the battery through negative pressure, shaking, tapping, and rotation. This method is suitable for conventionally compacted, conventionally sized batteries, but its effectiveness is limited for higher-compact and larger batteries. Furthermore, it requires specialized equipment, increasing development costs and resulting in low production efficiency. Additionally, excessively high negative pressure inevitably reduces battery liquid retention and may even damage the cell. Electrochemical methods primarily involve repeated pre-charge and discharge under low / micro current or pulsed current conditions. Under the influence of an electric field, organic components diffuse, and the charging process causes the negative electrode to expand, enhancing its liquid absorption capacity. However, this process is time-consuming (4-5 days), significantly increasing development costs. Therefore, new technological approaches need to be developed to improve the wetting capability and effect of large battery cells.

[0004] Existing technologies employ a two-step electrolyte injection strategy (first injecting 40%-60% of the volume, then injecting the resting volume completely) and vacuum injection, supplemented by physical extrusion, to shorten the battery resting time from 24 hours to 16 hours, thus improving the consistency of the wetting effect. This approach only uses pouch cells as the research model. While the physical extrusion method to accelerate electrolyte wetting is highly feasible for pouch cells, it is not suitable for cylindrical and prismatic cells due to their rigid casings, thus limiting its applicability. Furthermore, the use of pulse extrusion and rolling extrusion devices in this approach can negatively impact the stability of the battery's internal structure.

[0005] Therefore, there is a need to develop a method to improve the electrolyte wetting efficiency of large-size power batteries, to quickly improve the wettability of the electrolyte at the electrode interface, and to have a wide range of applications, applicable to both soft-pack and hard-shell batteries. Summary of the Invention

[0006] The purpose of this invention is to overcome the shortcomings of the aforementioned background technology and provide a method for improving the electrolyte wetting efficiency of large-size power batteries. This method rapidly improves the wettability of the electrolyte at the electrode interface and has a wide range of applications, suitable for cylindrical, pouch, and prismatic batteries. By improving the surface polarity of the non-active component conductive carbon, the surface energy at the electrolyte-electrode interface is reduced, thereby improving the wettability of the electrolyte at the electrode interface. Simultaneously, the use of two electrolytes with a significant concentration difference creates a clear diffusion gradient, accelerating the diffusion of the electrolyte within the electrode.

[0007] The technical solution of this invention is as follows: This application provides a method for improving the electrolyte wetting efficiency of large-size power batteries, comprising:

[0008] The conductive carbon is subjected to surface micro-oxidation treatment to reduce its contact angle with the electrolyte used in the selected battery model to meet the preset requirements, thus obtaining surface micro-oxidized conductive carbon.

[0009] The surface micro-oxidized conductive carbon is used to complete the assembly of large-size power batteries according to the selected battery model;

[0010] The electrolyte is injected in batches. The first injection is a pure solvent, and the second injection is a high-concentration electrolyte.

[0011] After encapsulation, allow it to stand to complete the impregnation process.

[0012] In the above scheme, by performing surface micro-oxidation treatment on the components of the high-pressure compaction electrode—using a smaller dosage of conductive carbon—the contact angle is reduced, thereby optimizing the solid-liquid phase contact interface and accelerating the spread of the electrolyte on the electrode surface. Simultaneously, the surface micro-oxidation treatment can, to some extent, reduce the size of the conductive carbon and increase its specific surface area, which helps to improve the compaction density of the electrode. Furthermore, by using a stepwise injection method, the maximum concentration difference is utilized as the diffusion driving force to accelerate the diffusion of the electrolyte in the electrode bulk phase, achieving rapid electrolyte wetting.

[0013] Preferably, the conductive carbon includes one or more of Super P, Ketjen black, acetylene black, carbon black, carbon nanotubes, carbon nanofibers, and graphene.

[0014] Preferably, the micro-oxidation treatment includes solution oxidation and / or high-temperature air oxidation.

[0015] The solution oxidation method includes: immersing conductive carbon in an oxidation solution at room temperature for 5-30 minutes; the oxidation solution is an aqueous solution containing one or more of hydrogen peroxide, nitric acid, sulfuric acid, and potassium permanganate; the concentration of the oxidation solution is 5-15 wt%; and washing and drying are performed after oxidation.

[0016] The high-temperature air oxidation method includes: oxidizing conductive carbon in air at a temperature of 100-250℃ for 5-30 minutes.

[0017] In the above solution oxidation method, oxidizing agents such as hydrogen peroxide, nitric acid, sulfuric acid, and potassium permanganate are used to achieve uniform and rapid oxidation of conductive carbon in a liquid environment at room temperature. After washing with deionized water, the carbon is dried at 60°C for 5-30 minutes to quickly obtain conductive carbon with micro-oxidation on the surface. The oxidation solution is an aqueous solution with a mass fraction of 5-15 wt%. This is because excessive concentration can easily lead to over-oxidation of some conductive agents, resulting in poor performance consistency; while excessively low concentration can lead to overly slow oxidation. Therefore, this range is selected to ensure appropriate oxidation of the conductive agent.

[0018] In the high-temperature air oxidation method described above, oxygen in the air is used to oxidize the conductive carbon. The temperature range is 100-250℃, and micro-oxidized conductive carbon can be rapidly obtained in 5-30 minutes. This is because excessively high temperatures can easily cause a large amount of conductive agent to be oxidized into carbon dioxide, while excessively low temperatures can easily prevent the oxidation from being achieved. Therefore, this range is chosen to ensure the appropriate level of oxidation.

[0019] Preferably, the preset requirement for the contact angle is: 30% ≥ Contact angle reduction rate ≥ 10%. During the contact angle test, a standard electrolyte of the selected battery model is used as the solvent. Oxidation is considered complete when the contact angle reduction rate is ≥ 10%, and a contact angle reduction rate ≤ 30% aims to ensure surface oxidation of the conductive agent while avoiding excessive oxidation. More preferably, 30% ≥ Contact angle reduction rate ≥ 20%.

[0020] Preferably, the large-size power battery has a battery capacity of ≥200Ah and a positive electrode compaction density of ≥2.5g / cm³. 3 The negative electrode compaction density is ≥1.6 g / cm³. 3 .

[0021] Preferably, the pure solvent for the first injection is one or more of ethylene carbonate, vinylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, methyl propyl carbonate, methyl acetate, ethyl propionate, ethyl butyrate, methyl formate, methyl acetate, and methyl butyrate.

[0022] Preferably, the high-concentration electrolyte for the second injection is obtained by dissolving a lithium salt in a solvent. The lithium salt is one or more of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium difluorophosphate, and lithium bis(trifluoromethanesulfonyl)imide. The solvent composition in the high-concentration electrolyte is consistent with the pure solvent used in the first injection.

[0023] Preferably, the lithium salt concentration in the high-concentration electrolyte injected in the second injection is 2-4 mol / L, and the total volume of the pure solvent from the first injection and the high-concentration electrolyte from the second injection is consistent with the electrolyte volume specified in the selected battery model. The volume and concentration of the two injections are consistent with the conventional injection volume, without increasing the electrolyte cost. Using an electrolyte with a significant concentration difference creates a clear diffusion gradient, accelerating the diffusion of the electrolyte within the electrode.

[0024] Preferably, the injection conditions are a dew point ≤ -40℃ and a vacuum condition at room temperature.

[0025] Preferably, the impregnation time is 8–24 hours. After encapsulation, the product is left to stand at 45°C to complete the impregnation process.

[0026] Preferably, during the immersion process, an electrochemical workstation is used to monitor the battery's internal resistance. Starting from 6 hours of immersion, the internal resistance value is measured every 1-2 hours thereafter. Immersion is considered complete when the deviation of three consecutive internal resistance values ​​is ≤5%. The deviation of each measured internal resistance value is calculated as |test value - mean| / mean * 100%, where the mean is the average of the three measured values. Impedance testing using the electrochemical workstation obtains the corresponding relationship between the battery's internal resistance values ​​at different immersion times, monitors the immersion effect, and quickly achieves efficient immersion.

[0027] The beneficial effects of this invention include:

[0028] 1. By optimizing only a small amount of conductive carbon on the electrode sheet, followed by stepwise electrolyte injection with different concentrations, surface micro-oxidation can be completed in just 5-30 minutes. This requires no major changes to existing battery manufacturing processes, resulting in lower investment costs. More efficient electrolyte wetting shortens production time and reduces production costs.

[0029] 2. Surface micro-oxidation of conventional conductive carbon improves the surface polarity of inactive components, reduces the surface energy of the electrolyte-electrode interface, thereby improving the wettability of the electrolyte at the electrode interface, reducing the contact angle and facilitating the diffusion and spreading of the electrolyte solvent on the high-compact electrode surface. Moreover, surface micro-oxidation can reduce the size of conductive carbon to a certain extent, increase its specific surface area, and help improve the compaction density of the electrode.

[0030] 3. In the electrolyte injection process, electrolytes with large concentration differences are injected in stages. The first injection uses pure solvent, and the second injection uses high-concentration electrolyte to maximize the concentration difference. Since the diffusion rate is positively correlated with the concentration difference, a significant diffusion gradient is formed, which can accelerate the diffusion of electrolyte in the bulk phase under a large concentration difference.

[0031] 4. Impedance testing using an electrochemical workstation allows for the determination of the corresponding internal resistance values ​​of batteries with different wetting times, enabling monitoring of the wetting effect and rapid achievement of efficient wetting. This facilitates the rapid establishment of large-scale data models to shorten the R&D cycle. This strategy is applicable to cylindrical, pouch, and prismatic batteries. Attached Figure Description

[0032] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this application and, together with the description, serve to explain the principles of this application.

[0033] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0034] Figure 1 This is a schematic diagram of the micro-oxidation treatment on the conductive carbon surface of this application.

[0035] Figure 2 Schematic diagram of existing one-step injection and step-by-step injection wetting in this application Detailed Implementation

[0036] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.

[0037] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0038] Current methods for improving electrolyte wetting effects have shortcomings such as poor universality, complex processes, and long processing times. For example, two-step electrolyte injection (first injecting 40%-60% of the volume, then injecting completely) followed by physical extrusion is not applicable to batteries with rigid casings such as cylindrical and prismatic batteries. For example, negative pressure, shaking, tapping, and rotation are not effective for high-compact and large-size batteries, and require the use of corresponding equipment, increasing development costs. For example, repeated pre-charge and discharge under conditions of small / micro current or pulse current takes a long time.

[0039] This application aims to provide a fast, efficient, universally applicable method for improving the electrolyte wetting efficiency of large-size power batteries without the need for additional equipment. The method improves the surface polarity of the non-active component—conductive carbon—through surface micro-oxidation, reduces the contact angle, and lowers the surface energy at the electrolyte-electrode interface, thereby improving the wettability of the electrolyte at the electrode interface. At the same time, the method assists by using two electrolytes with a large concentration difference to form a significant diffusion gradient, which accelerates the diffusion of the electrolyte inside the electrode.

[0040] This application discloses a method for improving the electrolyte wetting efficiency of large-size power batteries, comprising the following steps:

[0041] (1) The conductive carbon is subjected to surface micro-oxidation treatment. After treatment, the contact angle with the electrolyte used in the selected battery model reaches the preset requirement (30% ≥ contact angle reduction rate ≥ 10%), thus obtaining surface micro-oxidized conductive carbon.

[0042] (2) Assemble large-size power batteries by micro-oxidizing conductive carbon on the surface according to the selected battery model, with performance requirements of battery capacity ≥200Ah and positive electrode compaction density ≥2.5g / cm³. 3 Negative electrode compaction density ≥ 1.6 g / cm³ 3 ;

[0043] (3) Perform the liquid injection in batches. The first injection is a pure solvent, and the second injection is a high-concentration electrolyte.

[0044] (4) After encapsulation, the product is left to stand at 45°C for 8-24 hours to complete the impregnation process. The internal resistance value at different times is measured using an electrochemical workstation to monitor the impregnation effect.

[0045] In some embodiments, the conductive carbon in step (1) is selected from one of the following: conventional Super P, Ketjen black, acetylene black, carbon black, carbon nanotubes, carbon nanofibers, graphene, etc.

[0046] In some embodiments, the surface micro-oxidation treatment in step (1) can be carried out by solution oxidation or high-temperature air oxidation. The solution oxidation method is as follows: the conductive carbon is immersed in an oxidation solution at room temperature for 5-30 minutes. The oxidation solution is an aqueous solution containing one or more of hydrogen peroxide, nitric acid, sulfuric acid, and potassium permanganate. The oxidation solution is an aqueous solution with a mass fraction of 5-15%. After oxidation, the carbon is washed with deionized water and dried.

[0047] In some embodiments, the high-temperature air oxidation method includes: oxidizing conductive carbon in air at a temperature of 100-250°C for 5-30 minutes.

[0048] The effect of conductive carbon after surface micro-oxidation treatment is as follows Figure 1 As mentioned above, after micro-oxidation, more oxygen atoms are attached to the surface, which improves the surface polarity. When in contact with the electrolyte, the contact angle will be significantly smaller, reducing the surface energy of the electrolyte-electrode interface and thus improving the wettability of the electrolyte at the electrode interface.

[0049] In some embodiments, the contact angle test is performed using a standard electrolyte for the selected battery model as the solvent.

[0050] In some embodiments, the pure solvent used in the first injection of the electrolyte in step (3) is one or more of ethylene carbonate, vinylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, methyl propyl carbonate, methyl acetate, ethyl propionate, ethyl butyrate, methyl formate, methyl acetate, and methyl butyrate; the lithium salt used in the electrolyte for the second injection is one or more of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium difluorophosphate, and lithium bis(trifluoromethanesulfonyl)imide, and the solvent is consistent with the pure solvent composition of the first injection (i.e., the solvent in the high-concentration electrolyte is the same as the pure solvent of the first injection).

[0051] In some embodiments, the electrolyte concentration used in step (3) for the second electrolyte injection is 2-4 mol / L, and concentration diffusion allows the salt to migrate within the battery. The volume of the two injections is related to the concentration, ensuring that the total volume and concentration of the two injections are consistent with conventional electrolyte injection (conventional electrolyte concentration 1 mol / L, dosage 2-4 g / Ah). For example, if the electrolyte concentration of the second injection is 2 mol / L, the volume ratio of the two injections is 1:1; if the concentration of the second injection is 3 mol / L, the volume ratio of the two injections is 2:1; if the concentration of the second injection is 4 mol / L, the volume ratio of the two injections is 3:1. This does not increase the cost of the electrolyte at all.

[0052] Comparison of the wetting speed of one-step and step-by-step electrolyte injection for batteries, for example Figure 2 As shown, compared to directly injecting electrolyte into the high-voltage electrode in one step, the step-by-step electrolyte injection involves injecting only pure solvent in the first step. Pure solvent has low viscosity and can quickly wet the electrode. In the second step, high-concentration electrolyte is injected, and concentration diffusion occurs, allowing the electrolyte to efficiently wet the electrode.

[0053] In some embodiments, an electrochemical workstation is used to measure the battery internal resistance and record the changes in resistance over the immersion time. Testing begins after 6 hours of immersion and is performed every 1-2 hours thereafter. Monitoring ends when the deviation of the internal resistance value from three consecutive tests is ≤5%.

[0054] The present application is further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the application. Experimental methods in the following embodiments that do not specify specific conditions are generally determined according to national standards. If there is no corresponding national standard, then general international standards, conventional conditions, or conditions recommended by the manufacturer are followed.

[0055] Example 1

[0056] This application discloses a method for improving the electrolyte wetting efficiency of large-size power batteries, comprising the following steps:

[0057] (1) The conductive carbon Super P was subjected to surface micro-oxidation treatment. In this embodiment, the following high-temperature oxidation method was used for surface micro-oxidation treatment. The conductive carbon was oxidized in a muffle furnace at a temperature of 200°C for 8 minutes. After treatment, the contact angle reached the preset requirement (the contact angle reduction rate was 20%), and the conductive carbon with surface micro-oxidation was obtained.

[0058] (2) Assemble large-size power batteries by micro-oxidizing conductive carbon on the surface according to the selected battery model (square battery), with performance meeting the requirements of a battery capacity of 212Ah and a positive electrode compaction density of 2.6g / cm³. 3 The negative electrode compaction density is 1.6 g / cm³. 3 ;

[0059] (3) Perform two-step batch electrolyte injection. The first injection is a pure solvent (made of diethyl carbonate, dimethyl carbonate, and ethylene carbonate in a volume ratio of 1:1:1 and 1% by mass of vinylene carbonate, where 1% refers to the mass content of ethyleneene carbonate in the pure solvent). The second injection is a high-concentration electrolyte, namely a lithium salt (LiPF6) solution with a concentration of 2 mol / L. The solvent composition is consistent with the pure solvent of the first injection. The volume ratio of the first and second injections is 1:1 to ensure that the total volume and total concentration of the two injections are consistent with the conventional electrolyte injection of the selected battery model.

[0060] (4) After encapsulation, the internal resistance value was placed at 45°C to complete the impregnation process. The internal resistance value was measured at different times using an electrochemical workstation to monitor the impregnation effect. Starting from 6 hours of impregnation, the test was performed every 2 hours thereafter. The monitoring ended when the deviation of the internal resistance value in 3 consecutive tests was ≤5%. The total impregnation time was 16 hours.

[0061] Example 2

[0062] This application discloses a method for improving the electrolyte wetting efficiency of large-size power batteries, comprising the following steps:

[0063] (1) Surface micro-oxidation treatment was performed on the conductive carbon super P. In this embodiment, the following solution oxidation method was used for surface micro-oxidation treatment. The conductive carbon was immersed in an oxidation solution at room temperature for 20 minutes. The oxidation solution was an aqueous solution of hydrogen peroxide with a mass fraction of 5%. After oxidation, the carbon was washed with deionized water and dried. After treatment, the contact angle reached the preset requirement (contact angle reduction rate of 25%), and the conductive carbon with surface micro-oxidation was obtained.

[0064] (2) Assemble large-size power batteries by micro-oxidizing conductive carbon on the surface according to the selected battery model (square battery), with performance meeting the requirements of a battery capacity of 212Ah and a positive electrode compaction density of 2.6g / cm³. 3 The negative electrode compaction density is 1.8 g / cm³. 3 ;

[0065] (3) Perform two-step batch electrolyte injection. The first injection is a pure solvent (a mixture of diethyl carbonate, dimethyl carbonate, ethylene carbonate in a volume ratio of 1:1:1 and ethylene carbonate with a mass fraction of 1%). The second injection is a high-concentration electrolyte, namely a lithium salt (LiPF6) solution with a concentration of 3 mol / L. The solvent composition is consistent with the pure solvent of the first injection. The volume ratio of the first and second injections is 2:1 to ensure that the total volume and total concentration of the two injections are consistent with the conventional electrolyte injection of the selected battery model.

[0066] (4) After encapsulation, the internal resistance value was measured at 45°C to complete the impregnation process. The internal resistance value was measured at different times using an electrochemical workstation to monitor the impregnation effect. Starting from 6 hours of impregnation, the test was performed every 2 hours thereafter. The monitoring ended when the deviation of the internal resistance value in 3 consecutive tests was ≤5%. The total impregnation time was 18 hours.

[0067] Example 3

[0068] This application discloses a method for improving the electrolyte wetting efficiency of large-size power batteries, comprising the following steps:

[0069] (1) The conductive carbon super P was subjected to surface micro-oxidation treatment. In this embodiment, the following high-temperature oxidation method was used for surface micro-oxidation treatment. The conductive carbon was oxidized in a muffle furnace at a temperature of 180°C for 15 minutes. After treatment, the contact angle reached the preset requirement (the contact angle reduction rate was 26%), and the conductive carbon with surface micro-oxidation was obtained.

[0070] (2) Assemble large-size power batteries by micro-oxidizing conductive carbon on the surface according to the selected battery model (square battery), with performance meeting the requirements of a battery capacity of 290Ah and a positive electrode compaction density of 2.7g / cm³. 3 The negative electrode compaction density is 1.6 g / cm³. 3 ;

[0071] (3) Perform two-step batch electrolyte injection. The first injection is a pure solvent (a mixture of diethyl carbonate, dimethyl carbonate, ethylene carbonate in a volume ratio of 1:1:1 and ethylene carbonate with a mass fraction of 1%). The second injection is a high-concentration electrolyte, namely a lithium salt (LiPF6) solution with a concentration of 4 mol / L. The solvent composition is consistent with the pure solvent of the first injection. The volume ratio of the first and second injections is 3:1 to ensure that the total volume and total concentration of the two injections are consistent with the conventional electrolyte injection of the selected battery model.

[0072] (4) After encapsulation, the internal resistance value was placed at 45°C to complete the impregnation process. The internal resistance value was measured at different times using an electrochemical workstation to monitor the impregnation effect. Starting from 6 hours of impregnation, the test was performed every 2 hours thereafter. The monitoring ended when the deviation of the internal resistance value in 3 consecutive tests was ≤5%. The total impregnation time was 22 hours.

[0073] Example 4

[0074] This application discloses a method for improving the electrolyte wetting efficiency of large-size power batteries, comprising the following steps:

[0075] (1) Surface micro-oxidation treatment was performed on the conductive carbon super P. In this embodiment, the following solution oxidation method was used for surface micro-oxidation treatment. The conductive carbon was immersed in an oxidation solution at room temperature for 15 minutes. The oxidation solution was an aqueous solution of potassium permanganate with a mass fraction of 5%. After oxidation, the carbon was washed with deionized water and dried. After treatment, the contact angle reached the preset requirement (contact angle reduction rate of 20%), and the conductive carbon with surface micro-oxidation was obtained.

[0076] (2) Assemble large-size power batteries by micro-oxidizing conductive carbon on the surface according to the selected battery model (square battery), with performance meeting the requirements of a battery capacity of 290Ah and a positive electrode compaction density of 2.7g / cm³. 3 The negative electrode compaction density is 1.8 g / cm³. 3 ;

[0077] (3) Perform two-step batch electrolyte injection. The first injection is a pure solvent (a mixture of diethyl carbonate, dimethyl carbonate, ethylene carbonate in a volume ratio of 1:1:1 and ethylene carbonate with a mass fraction of 1%). The second injection is a high-concentration electrolyte, namely a lithium salt (LiPF6) solution with a concentration of 4 mol / L. The solvent composition is consistent with the pure solvent of the first injection. The volume ratio of the first and second injections is 3:1 to ensure that the total volume and total concentration of the two injections are consistent with the conventional electrolyte injection of the selected battery model.

[0078] (4) After encapsulation, the internal resistance value was placed at 45°C to complete the impregnation process. The internal resistance value was measured at different times using an electrochemical workstation to monitor the impregnation effect. Starting from 6 hours of impregnation, the test was performed every 2 hours thereafter. The monitoring ended when the deviation of the internal resistance value in 3 consecutive tests was ≤5%. The total impregnation time was 24 hours.

[0079] Comparative Example 1 (Conductive agent not oxidized, electrolyte component injected)

[0080] This comparative example presents a method for improving the electrolyte wetting efficiency of large-size power batteries, comprising the following steps:

[0081] (1) Assemble a large-size power battery using conductive carbon super P according to the selected battery model (prismatic battery), with performance meeting the requirements of a battery capacity of 212Ah and a positive electrode compaction density of 2.6g / cm³. 3 The negative electrode compaction density is 1.6 g / cm³. 3 .

[0082] (2) A two-step batch electrolyte injection process is performed, using the same electrolyte composition for both injections, i.e., an electrolyte with a concentration of 1 mol / L. The lithium salt is LiPF6, and the solvent is a mixture of diethyl carbonate, dimethyl carbonate, and ethylene carbonate in a volume ratio of 1:1:1, along with 1% by mass of vinylene carbonate. The volume ratio of the first and second injections is 9:1, and the total volume of the injected electrolyte is consistent with the conventional electrolyte injection for the selected battery model.

[0083] (3) After encapsulation, the internal resistance value was placed at 45°C to complete the impregnation process. The internal resistance value was measured at different times using an electrochemical workstation to monitor the impregnation effect. Starting from 6 hours of impregnation, the test was performed every 2 hours thereafter. The monitoring ended when the deviation of the internal resistance value in 3 consecutive tests was ≤5%. The total impregnation time was 48 hours.

[0084] Comparative Example 2

[0085] This comparative example presents a method for improving the electrolyte wetting efficiency of large-size power batteries, comprising the following steps:

[0086] (1) Assemble a large-size power battery using conductive carbon super P according to the selected battery model (prismatic battery), with performance meeting the requirements of a battery capacity of 290Ah and a positive electrode compaction density of 2.7g / cm³. 3 The negative electrode compaction density is 1.8 g / cm³. 3 .

[0087] (2) Perform a two-step batch electrolyte injection, using the same electrolyte composition for both injections, i.e., an electrolyte with a concentration of 1 mol / L. The lithium salt is LiPF6, and the solvent is diethyl carbonate, dimethyl carbonate, and ethylene carbonate in a volume ratio of 1:1:1, plus 1% by mass of vinylene carbonate. The volume ratio of the first and second injections is 9:1, and the total volume of the injected electrolyte is consistent with the conventional electrolyte injection for the selected battery model.

[0088] (3) After encapsulation, the internal resistance value was placed at 45°C to complete the impregnation process. The internal resistance value was measured at different times using an electrochemical workstation to monitor the impregnation effect. Starting from 6 hours of impregnation, the test was performed every 2 hours thereafter. The monitoring ended when the deviation of the internal resistance value in 3 consecutive tests was ≤5%. The total impregnation time was 72 hours.

[0089] Performance testing

[0090] The electrolyte retention rate and yield of the batteries from Examples 1-4 and Comparative Examples 1-2 were tested. The electrolyte retention rate test conditions were to determine the amount of electrolyte injected and weigh the cells before and after electrolyte injection. The yield rate test conditions were to cycle the cells three times at room temperature (1°C) and the absolute value of the difference between the tested capacity and the rated capacity should not exceed 5% of the rated capacity. The results are shown in Table 1 below.

[0091] Table 1 Performance Data Table

[0092]

[0093] As can be seen from Table 1, the electrolyte retention rate of the battery assembled in this application is at least 5% higher than that of the comparative example, and the time required for complete immersion is about half or one-third of that of the comparative example. This indicates that the synergistic strategy of conductive agent oxidation and different electrolyte injection provided in this application can achieve rapid diffusion of electrolyte inside the battery cell. The yield rate of this application is 100%, which is much higher than that of the comparative example, indicating that this application helps to improve the current practical problems of difficult and time-consuming electrolyte injection and immersion in large battery cells.

Claims

1. A method for improving the electrolyte infiltration efficiency of a large-size power battery, characterized in that: include: Conductive carbon is subjected to surface micro-oxidation treatment to reduce its contact angle with the electrolyte used in the selected battery model to meet the preset requirements, thereby obtaining surface micro-oxidation conductive carbon; The surface slightly oxidized conductive carbon is assembled into large-size power batteries according to the selected battery model; Two batch injections are performed, the first injection is pure solvent, and the second injection is high-concentration electrolyte; After encapsulation, let it stand to complete the wetting process.

2. The method for improving the electrolyte infiltration efficiency of a large-size power battery according to claim 1, characterized in that: The conductive carbon includes one or more of Super P, Ketjen black, acetylene black, carbon black, carbon nanotubes, carbon nanofibers, and graphene.

3. The method for improving the electrolyte infiltration efficiency of a large-size power battery according to claim 1, characterized in that: The micro-oxidation treatment includes solution oxidation and / or high temperature air oxidation. The solution oxidation method comprises: the conductive carbon is immersed in an oxidation solution at room temperature for 5-30 minutes, the oxidation solution is an aqueous solution containing one or more of hydrogen peroxide, nitric acid, sulfuric acid, and potassium permanganate, the concentration of the oxidation solution is 5-15wt%, and the conductive carbon is washed and dried after the oxidation is completed; The high temperature air oxidation method comprises: oxidizing the conductive carbon in air at a temperature of 100-250° C. for 5-30 minutes.

4. The method for improving the electrolyte infiltration efficiency of a large-size power battery according to claim 1, characterized in that: The preset requirement for the contact angle is: 30% ≥ contact angle reduction rate ≥ 10%.

5. The method for improving the electrolyte infiltration efficiency of a large-size power battery according to claim 1, characterized in that: The battery capacity of the large-size power battery is ≥200Ah, and the positive electrode compaction density is ≥2.5g / cm 3 , negative electrode compaction density ≥1.6g / cm 3 .

6. The method for improving the electrolyte infiltration efficiency of a large-size power battery according to claim 1, characterized in that: The pure solvent for the first injection is one or more of ethylene carbonate, vinylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, methyl acetate, ethyl propionate, ethyl butyrate, methyl formate, methyl acetate, and methyl butyrate.

7. The method for improving the electrolyte infiltration efficiency of a large-size power battery according to claim 1, characterized in that: The high-concentration electrolyte for the second injection is obtained by dissolving a lithium salt in a solvent. The lithium salt is one or more of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium difluorophosphate and lithium bis(trifluoromethanesulfonyl)imide. The solvent composition in the high-concentration electrolyte is consistent with the pure solvent of the first injection.

8. The method for improving the electrolyte infiltration efficiency of a large-size power battery according to claim 7, characterized in that: The lithium salt concentration in the high-concentration electrolyte of the second injection is 2-4 mol / L, and the total volume of the pure solvent of the first injection and the high-concentration electrolyte of the second injection is consistent with the electrolyte volume specified in the selected battery model.

9. The method for improving the electrolyte infiltration efficiency of a large-size power battery according to claim 1, characterized in that: The total infiltration time is 8-24h.

10. The method for improving the electrolyte infiltration efficiency of a large-size power battery according to claim 1 or 9, characterized in that: During the infiltration process, an electrochemical workstation was used to monitor the internal resistance of the battery. The internal resistance value was tested starting from 6 hours of infiltration and then every 1-2 hours. When the deviation of the internal resistance value was ≤5% for three consecutive tests, the infiltration was completed.

Citation Information

Patent Citations

  • Treatment method of carbon felt for vanadium batteries

    CN103066287A

  • Graphene based composite conductive agent, its preparation method and application in lithium ion battery

    CN103560248A

  • Micro-oxidized conductive carbon black supported nano metal bismuth catalyst and application thereof

    CN109908887A

  • Preparation method and application of oxidation nitrogen-doped carbon nanotube array cluster / flexible carbon fiber material integrated electrode

    CN112421055A

  • Electrolyte injection method and lithium ion battery

    CN113629365A